Pengaruh Penerapan Konsep Good Corporate Governance Dan Penerapan Sistem Informasi Akuntansi Pada Persepsi Kinerja Keuangan (Studi Kasus Pada LPD di Kecamatan Karangasem) - Ni Ketut Enji Pebrianti; I Wayan Gde Wahyu Purna Anggara (Universitas Dian Nuswantoro, 2022)
Financial performance is a tool used by company to measure its ability in the field of financial management. An organization or institution that has good financial performance will increase trust people who have an interest in the institution or commonly referred as stakeholders, to invest their capital. So the financial performance of an institution must be maintained so that it remains good. This study purpose to know the effect of application concept of good corporate governance and application of accounting information systems on perceptions financial performance. This research at the Lembaga Perkreditan Desa (LPD) in Karangasem District. The method of determining the sample is purposive sampling method with non-probability sampling technique. The method of collection data using questionnaire with 5-point Likert scale by visiting directly Lembaga Perkreditan Desa (LPD). The data analysis technique used was Statistical Package for Social Science (SPSS) 26 for Windows program. The results of this study indicate that the application of the concept of good corporate governance and the application of accounting information systems have a significant positive effect on the perception of financial performance in case studies at Lembaga Perkreditan Desa ( LPD) in Karangasem District. This means that whenÂ the application of the concept of good corporate governance and the application of accounting information systems is beter, so the financial performance of the LPD will be better too. The implications of this research are expected to be able provide benefits and an overview of the importance of applying the concept of good corporate governance and implementing accounting information systems for an LPD in improving its financial performance.